1997
DOI: 10.1152/ajpgi.1997.272.3.g408
|View full text |Cite
|
Sign up to set email alerts
|

CD18 integrin and CD54-dependent neutrophil adhesion to cytokine-stimulated human hepatocytes

Abstract: We investigated the hypothesis that CD54 (intercellular adhesion molecule-1) expressed on hepatocytes will support beta2-integrin (CD18)-dependent adhesion of neutrophils. An in vitro model using C3A cells (a human hepatoblastoma cell line exhibiting many characteristics of normal hepatocytes) and human neutrophils was utilized. C3A cells were stimulated with interleukin-1beta (IL-1beta), tumor necrosis factor-alpha, or interferon-gamma (IFN-gamma) for 24 h to induce expression of CD54, and adhesion of neutrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 0 publications
0
50
0
2
Order By: Relevance
“…12 However, others have shown that pharmacological doses of IFN-␥ may produce anti-inflammatory effects, 18 consistent with our finding that INFRG KO mice suffered even more severe IRI damage than WT. Indeed, IFN-␥ may exert cytoprotective functions by modulating the production of proteases/reactive oxygen species from KC, 19 by decreasing CD54 20 or E/P selectin 21 expression. Although both IFNs stimulate the production of IFN-inducible proteins, 22 our results have revealed that type I IFN selectively mediated liver CXCL10 induction.…”
Section: Discussionmentioning
confidence: 99%
“…12 However, others have shown that pharmacological doses of IFN-␥ may produce anti-inflammatory effects, 18 consistent with our finding that INFRG KO mice suffered even more severe IRI damage than WT. Indeed, IFN-␥ may exert cytoprotective functions by modulating the production of proteases/reactive oxygen species from KC, 19 by decreasing CD54 20 or E/P selectin 21 expression. Although both IFNs stimulate the production of IFN-inducible proteins, 22 our results have revealed that type I IFN selectively mediated liver CXCL10 induction.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, myeloperoxidase (halide form, such as Cl -) released from neutrophils changes hydrogen peroxide (H2O2) into hypochlorous acid (HOCl), which is a potent oxidant. These oxidants can directly cause liver cell damage and/or induce protease-mediated injury through inactivation of the endogenous anti-protease system [15,16] , suggesting that anti-oxidant or anti-protease therapy would be helpful for preventing IRI.…”
Section: Kcs and Neutrophilsmentioning
confidence: 99%
“…One of us (C. W. S.) has recently reported on the molecules involved in the adherence of neutrophils to hepatocytes in vitro. In the absence of exogenous chemotactic activation, neutrophils adhered to cytokine-treated hepatocytes via LFA-1 and ICAM-1 [49]. Adhesion via activated Mac-1 is subsequently required for the release of proteolytic enzymes and reactive oxygen species by neutrophils that are cytotoxic to parenchymal cells in vitro (e.g., cardiac myocytes or hepatocytes).…”
Section: Comparison Of Homotypic and Heterotypic Adhesionmentioning
confidence: 99%